Prevalence of Medication Errors and the Associated Factors: A Prospective Observational Study Among Cancer Patients at Mbarara Regional Referral Hospital - Dorothy, Abigaba; Yadesa, Tadele Mekuriya; Atukunda, Esther Cathyln (Cancer Management and Research, 2021)
Background: Medication error is one of the most common medical errors in the practice of modern medicine. Among cancer patients receiving chemotherapy, medication errors can be potentially harmful given the narrow therapeutic index, complex dosing, and toxic nature of anti-cancer drugs. Objective: This study aimed to determine the incidence and factors associated with medication errors among cancer patients. Methods: The study was a prospective observational study carried out at the cancer unit of Mbarara Regional Referral Hospital, Southwestern Uganda. The study included 110 participants, both adults and children receiving chemotherapy. The study was carried out for a period of five months from January to May 2020. A checklist was used to collect patient, medication, and disease information to identify the prescription, transcription, dispensing, and administration errors. Results: Of the 110 participants, 52 (47.3%) experienced a total of 78 medication errors (MEs). Of these, 33 (42.31%) were prescription errors, 29 (37.18%) administration errors, 9 (11.54%) transcription errors, and 7 (8.97%) dispensing errors. In the adjusted logistic regression of factors associated with medication errors, urban residents (aOR, 4.59; 95% CI, 1.08, 19.53, p= 0.039) and educated participants (at secondary level) (aOR, 10.51; 95% CI, 1.43, 77.14, p= 0.021) had a significantly higher risk of experiencing medication errors. Participants treated with alkylating agents (aOR, 2.87; 95% CI, 1.07, 7.72, p= 0.036) had a greater risk of experiencing medication errors when compared to other classes of chemotherapy. Conclusion: The incidence of medication errors among cancer patients was high in Mbarara Regional Referral Hospital. Prescription errors were the most common type of error followed by administration errors, and dispensing errors were the least common. Residence, education level, and alkylating agent chemotherapy were significantly associated with occurrence of medication errors.
Keywords: Prevalence; Medication error; Associated factors; Cancer; Mbarara